2012
DOI: 10.1590/s1415-43662012000500007
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de cultivares de cenoura em função da água no solo

Abstract: RESUMO Objetivou-se, com este estudo, avaliar o efeito de diferentes tensões da água no solo sobre a produção de duas cultivares de cenoura irrigadas por gotejamento. O experimento foi conduzido em Lavras, Minas Gerais (21º 14' S, 45º 00' W e 918,8 m), no período de julho a outubro de 2010. O delineamento experimental utilizado foi em blocos casualizados, em esquema fatorial 2 x 6, com quatro repetições. Os tratamentos se constituíram de duas cultivares de cenoura, cultivar não híbrida Nantes e cultivar hibrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
5
1
8
Order By: Relevance
“…The extreme tensions (12 and 70 kPa) obtained the lowest efficiencies with values of 383.7 and 449.78 kg ha -1 mm -1 , respectively. Some studies in specialized literature, conducted with other vegetables, demonstrate that an increase in water tension and/ or decrease of applied water depth leads to growing efficiency values (LIMA JÚNIOR et al, 2012b;VILAS BOAS et al, 2011); however, in this study, it was observed up to 45 kPa.…”
Section: Variationcontrasting
confidence: 69%
“…The extreme tensions (12 and 70 kPa) obtained the lowest efficiencies with values of 383.7 and 449.78 kg ha -1 mm -1 , respectively. Some studies in specialized literature, conducted with other vegetables, demonstrate that an increase in water tension and/ or decrease of applied water depth leads to growing efficiency values (LIMA JÚNIOR et al, 2012b;VILAS BOAS et al, 2011); however, in this study, it was observed up to 45 kPa.…”
Section: Variationcontrasting
confidence: 69%
“…It should be underscored that several other crops, such as lettuce (PUTTI et al, 2015), carrot (LIMA JUNIOR et al, 2012), sunflower (SILVA et al, 2011, sugarcane (VIEIRA et al, 2014), red pepper (ARAGÃO et al, 2011) and sweet potato (MANTOVANI et al, 2013) provided a quadratic response to different reposition rates.…”
Section: Resultsmentioning
confidence: 99%
“…Cada parcela experimental foi constituída de um canteiro com dimensões de 1,0 x 0,6 m. Em cada canteiro foi demarcado três linhas espaçadas de 0,20 m e o espaçamento entre plantas foi 0,08m. Os níveis de tensão de água no solo foi definido com base nos dados de Lima Júnior et al (2012).…”
Section: Methodsunclassified